IFPRI's Strategy for Africa - International Food Policy Research Institute (International Food Policy Research Institute, 2009)
In January 2007, the International Food Policy Research Institute (IFPRI) published its first Africa Strategy, the first of any region. That first edition of the strategy was completed after a thorough review of the institute’s activities in the region and a series of consultations with policy researchers and analysts and other key stakeholder groups in Africa, including a major dissemination conference held in Dakar, Senegal in January 2007. The last edition was completed against the backdrop of several major initiatives that had brought renewed attention and commitment to economic development and food and nutrition security in Africa, and emergence of the longest economic and agricultural growth recovery in the continent since the 1960s. The strategy emphasized the needs and challenges of sustaining and accelerating growth to reach the poverty and hunger reduction Millennium Development Goal (MDG). Since then, new developments in the global food and financial markets, responses by African countries to these developments, and their progress in efforts to implement the Comprehensive Africa Agriculture Development Program (CAADP) have resulted in changes with potential long term strategic consequences. The current edition of the Africa strategy document describes: recent developments in IFPRI’s work in Africa; recent trends and prospects for growth and food and nutrition security in Africa; IFPRI’s strategy for Africa; research, communications, and capacity-building priorities; IFPRI’s operational emphasis; and the institutional response.